Laboratory, Radiological, And Anesthetic Considerations In The Management Of Miliary Tuberculosis With Respiratory Compromise-An Updated Review (The Review of Diabetic Studies, 2024)
Background: Miliary tuberculosis (TB) is a severe disseminated form of Mycobacterium tuberculosis infection characterized by hematogenous spread and multisystem involvement. Its nonspecific presentation often delays diagnosis and increases morbidity and mortality.Aim: To provide an updated review of the laboratory, radiological, anesthetic, and clinical considerations in diagnosing and managing miliary TB, particularly in patients presenting with respiratory compromise.Methods: This review synthesizes current evidence on epidemiology, pathophysiology, clinical manifestations, diagnostic modalities, and management strategies, drawing from microbiological, immunological, histopathological, and imaging-based investigations.Results: Miliary TB exhibits protean manifestations involving pulmonary and extrapulmonary organs, often requiring combined laboratory abnormalities, characteristic imaging, and molecular confirmation for diagnosis. Standard antitubercular therapy remains the cornerstone of treatment, with extended regimens recommended for CNS, skeletal, and immunocompromised cases. Complications include ARDS, MODS, and neurological involvement, all associated with increased mortality. Early diagnosis, multidisciplinary management, and vigilant monitoring significantly improve outcomes.Conclusion: Miliary TB demands high clinical suspicion and integrated diagnostic approaches. Early initiation of therapy, tailored management in organ‑specific involvement, and multidisciplinary care are essential to reducing mortality and enhancing patient outcomes.